1992
DOI: 10.1080/15298669291360030
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Effects of Inhaled Zinc Oxide in Human Subjects, Guinea Pigs, Rats, and Rabbits

Abstract: Occupational exposure to freshly formed zinc oxide (ZnO) particles (less than 1.0 micron aerodynamic diameter) produces a well-characterized response known as metal fume fever. An 8-hr threshold limit value (TLV) of 5 mg/m3 has been established to prevent adverse health effects because of exposure to ZnO fumes. Because animal toxicity studies have demonstrated pulmonary effects near the current TLV, the present study examined the time course and dose-response of the pulmonary injury produced by inhaled ZnO in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 0 publications
4
42
0
Order By: Relevance
“…Their composition consists of elemental carbon particles (10 -100 nm) onto which is adsorbed a large number of organic compounds through a nucleation phenomenon (Gordon et al 1992) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their composition consists of elemental carbon particles (10 -100 nm) onto which is adsorbed a large number of organic compounds through a nucleation phenomenon (Gordon et al 1992) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by an obstruction, not completely reversible and often progressive. The disease is associated with an abnormal inflammatory response of branches to particles, harmful substances or gas (Gordon et al 1992). The high levels of air pollution affect lung function; there is evidence that air pollution by diesel engine particles (DEP) is associated with a decline in respiratory function (Abbey et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration was ultimately deemed below the level where acute systemic effects occur. In earlier papers, the same research group and another reported observing symptoms of metal fume fever in healthy volunteers exposed to 4.5, 5 and 33 mg/m 3 ZnO dust, which are concentrations above the 2 mg/m 3 TLV for ZnO [67][68][69][70][71]. In these studies, the ZnO particles had average diameters of 300 nm (Fine and Gordon) and 170 nm (Kuschner), the latter having primary particle sizes of 8-40 nm.…”
Section: Controlled Human Volunteer Inhalation Studiesmentioning
confidence: 99%
“…Metal fume fever, a well-documented acute disease induced by intense inhalation of metal oxides, especially zinc, impairs pulmonary function but does not progress to chronic lung disease (Brown 1988;Drinker and Drinker 1928;Malo et al 1990). Symptoms generally appear within a few hours after acute exposure, usually with dryness of the throat and coughing (Drinker et al 1927b Lam et al 1982 Zinc oxide Lam et al 1985 Zinc oxide Lam et al 1988 Zinc oxide Gordon et al 1992 Zinc oxide Blanc et al 1991 Zinc oxide…”
Section: Respiratory Effectsmentioning
confidence: 99%
“…In a single-blind experiment, exposure of subjects to 3.9 mg zinc/m 3 as zinc oxide resulted in sore throat and chest tightness but no impairment of pulmonary function (Gordon et al 1992). It is speculated that subjects in other studies may have been less susceptible because of the development of tolerance to zinc (Gordon et al 1992).…”
mentioning
confidence: 99%